EXPERIMENTAL MODELING OF SATELLITE SOLAR POWER SYSTEM BASED ON PULSE WIDTH MODULATION CONTROLLED BOOST CONVERTER - Ali Mahmood Jasim; Yuri Alekseevich Shepetov (Авіаційно-космічна техніка та технологія, 2017)
The object of this work is the experimental confirmation of the properties of the satellite solar plant based of photovoltaic (PV) converters with a DC-DC Converter controlled by pulse-width modulation (PWM) device for constant tracking of maximum power point (MPP) of the power plant. The results of the experiment confirmed simulation results, derived previously through using the mathematical model in Matlab/Simulink. In the work is proposed new more effective algorithm for solar PV MPP tracking based on combination of few known methods. First working point is chosen by the open-circuit voltage coefficient, next points are searched by the hill-climbing method.